Impact of Contextual Factors on the Social Representation of Disability Among Students in Inclusive Junior High Schools - Harma, Kahina; Vernay, Frédérique; Marrone, Thierry; Gombert, Anne; Roussey, Jean-Yves (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2018)
This article explores the social representation of disability and the stereotypes held by nondisabled students. We were particularly interested in how these might change as a result of the interaction between contact, visibility and hindrance. We recruited 549 junior high students from schools that included pupils with disabilities. Results showed that social representation and disability stereotypes were indeed contingent upon the interaction of the three factors. The wheelchair, which was at the core of the student’s social representation of handicap at the beginning of the year, eased out and was replaced by references to mental disability and/or other terms when there was direct contact with a disabled peer. In the case of indirect contact, the disability had to be visible to observe similar results. Concerning disability stereotypes, the majority of participants initially attributed negative personality traits to people with disabilities and expressed negative emotions towards them. There was a tendency for them to become less negative under certain conditions at the year’s end. We discuss these results and their implications.